ANALISIS KARAKTER TOKOH DALAM NOVEL "LEBIH SENYAP DARI BISIKAN" KARYA ANDINA DWIFATMA - Hasibuan, Rabibtah Hasanah; Purba, Alfitriana (Jurnal Bahastra, 2022)
The Novel More Silent than a Whisper By Andina dwifatma is a good literary work and is interesting to read. In the novel there are several problems so that there are several characters in it. This study aims to describe the characters contained in the novel. This study uses a descriptive qualitative method. The source of data in this study was obtained from a novel "More Quiet Than a Whisper" by Andina Dwifatma which was published in 2021 and is her second novel after a season and another season in 2013. Data collection was carried out using reading, note-taking and library techniques to make it easier get the data results. Data analysis was carried out by means of data reduction, data presentation and drawing conclusions. The data analysis was carried out to make it easier to analyze, because after the data was reduced or selected important things, the next step was to present the data in a shorter description and finally draw conclusions to obtain evidence that supports data collection. In this study, it is focused only on the main characters, namely Amara and Baron who have different characteristics. Amara is a woman with a character who is responsible for her life choices but feels anxious every day. Meanwhile, Baron is a man who is selfish and ambitious about what he wants.